Effects of agricultural and urban impacts on macroinvertebrates assemblages in streams (Rio Grande do Sul, Brazil) - Luiz Ubiratan Hepp; Silvia V. Milesi; Cristiane Biasi; Rozane M. Restello (Zoologia (Curitiba), 2010)
This study evaluates the effects of agricultural and urban activities on the structure and composition of benthic communities of streams in the state of Rio Grande do Sul, Brazil. Benthic macroinvertebrates were collected in streams influenced by urbanization and agriculture and in streams with no anthropogenic disturbances (reference streams). Organism density was superior in urban streams when compared with streams in the other two areas. The taxonomic richness and Shannon diversity index were higher in reference streams. The benthic fauna composition was significantly different among land uses. The classification and ordination analyses corroborated the results of variance analyses demonstrating the formation of clusters corresponding to streams with similar land use. Seasonality was also found to influence the benthic community, though in a lesser degree than land use.